Parental leave regulations, mothers' labor force attachment and fathers' childcare involvement: evidence from a natural experiment - Jochen Kluve; Marcus Tamm (Journal of Population Economics, 2013)
In 2007, Germany implemented a generous parental leave regulation in order to make parenthood more attractive and more compatible with a working career, especially for mothers. We evaluate the reform using a natural experiment that compares outcomes of parents with children born shortly after and before the coming into effect of the law, and find a significant decrease in mothers' employment probability during the 12~months after giving birth, and an increase in mothers' employment probability after the transfer expires. The implementation of two daddy months is currently not reflected in significant changes in fathers' time devoted to childcare.
Additional information: This is the author's version of a work that was accepted for publication in Journal of Population Economics. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Journal of Population Economics; 26 (3), 2013 , pp. 983-1005 and is online available at http://dx.doi.org/ 10.1007/s00148-012-0404-1
Keywords: 330; Parental leave; Natural experiment; Female labor market participation